NOVEL ATTRACTANTS OF GALLERIA-MELLONELLA L (LEPIDOPTERA-PYRALIDAE-GALLERIINAE) - (:unkn) unknown (EDITIONS SCIENTIFIQUES ELSEVIER, 1993)
Various synthetic esters were tested for their attractiveness to females of Galleria mellonella in comparison with n-nonanal, a component of the sex pheromone of Galleria mellonella. It has been shown that methyl octanoate, ethyl octanoate and methyl decanoate attract females. Particularly, methyl octanoate is as effective as n-nonanal in bioassay and could be a potential pest control agent.
Keywords: GALLERIA-MELLONELLA; SEX PHEROMONE; ATTRACTANT; CHEMICAL CONTROL; SEX-PHEROMONE; MOTH; IDENTIFICATION